Implementación de un sistema de gestión de mantenimiento de equipos neonatales para un establecimiento de Essalud región Lima usando reconocimiento óptico de caracteres y modelo Weibull - Anaya Medina, Jhonatan Junnior (2020)
This research work proposes an alternative solution to the problem of the stableness of Essalud Lima region due to the lack of monitoring and maintenance control mechanisms for neonatal respiratory care equipment, which directly impacts the health of newborns in this hospital and that require assistance from this equipment. The proposed solution uses a Mobile Vision-based OCR algorithm, which allows you to identify the computer's numeric code in the field using an Android app on the mobile phone and then use the Weibull model, to determine the probability of computer failure at that time. The system uses the average time between failures obtained from the historical information of each computer to calculate the current probability of failure and the maximum operating point, which will be recalculated each time the equipment is scanned. Using the optical character recognition system resulted in a detection accuracy of 88%. Finally, the findings of the research and some suggestions for improvement for future work are shown.